Il dolo nella bancarotta Alla ricerca della tipicità soggettiva della fattispecie patrimoniale - MINICUCCI, GHERARDO (Premio Tesi di Dottorato, 2018)
This volume covers the role and policy efficacy of fraud within the system of bankruptcy crimes, focusing on the factual circumstances of the several indictments relating to it according to their their historical evolution; the traditional attention given to the declaratory judgement is replaced by the conceptual division between 'bankruptcy', 'insolvency' and 'financial difficulties', thus also enhancing the impact of the other insolvency procedures. The critical review of the individual criminal figures is oriented towards finding the minimum amount of fraud of each individual type of fraudulent bankruptcy, as a subjective typicality correction for the deficiencies of the offence. The investigation, which has turned into a broader reflection on the psychological aspect, aims at setting the coordinates for a possible reform of the volume's subject.